Systematic literature review to identify prognostic factors of efficacy and safety outcomes of chimeric antigen receptor T-Cell therapies in diffuse large B-Cell lymphoma - Schleifenbaum, Julia K.; Heger, Jan-Michel; Jost, Jonas; Rosato, Umberto; Riou, Sybille; Borchmann, Peter; Walzer, Stefan; Mahlich, Jörg (Journal of cancer research and clinical oncology, 2025)
Purpose To identify and summarize clinical factors influencing the efficacy and safety outcomes of CAR-T cell therapies in patients with diffuse large B-cell lymphoma (DLBCL) through a systematic literature review. Methods We performed a systematic literature review to identify factors impacting the efficacy and safety of CAR-T therapies in DLBCL. Articles were searched in PubMed, Cochrane, and EMBASE databases. Key outcomes, including progression-free survival (PFS), overall survival (OS), complete response rate (CRR), objective response rate (ORR), duration of response (DoR), best overall response (BOR), and safety measures (e.g., Immune Effector Cell-Associated Neurotoxicity Syndrome [ICANS], and Cytokine Release Syndrome [CRS]), were extracted according to PRISMA guidelines. A total of 712 articles were identified, with 185 selected for full-text screening. Ultimately, 79 articles met inclusion criteria. Exclusions were primarily due to the absence of relevant outcome data or publication type. Results This review highlights several factors that may influence the efficacy and safety of CAR-T therapies in DLBCL, including Eastern Cooperative Oncology Group Performance Status (ECOG PS), International Prognostic Index (IPI) score, disease histology, Ann Arbor disease stage, and elevated LDH levels. Conclusion The findings of this review can assist clinicians in refining treatment strategies and improving patient outcomes in DLBCL by incorporating these key influencing factors.